Uslub Muqabalah (Definition, Forms and Objectives) - Sriwahyuni; Mohamad Harjum (Penerbit Hellow Pustaka, 2025)
This research provides an in-depth discussion of Uslūb Muqābalah, a rhetorical style in Arabic that involves contras or opposition of meaning within one or two interconnected sentences. The study aims to describe the definition of uslūb muqābalah, identify its varios forms, and explain its rhetorical and stylistic purposes in classical and contemporary Arabic texts. The research uses a descriptive-analytical approach by examining examples from the Qur’and Arabic literary works. The findings show that uslūb muqābalah not only enhances the aesthetic structure of sentences but also strengthens meaning through sharp contrasts, creates a powerful rhetorical effect, and aids in the reader’s pr listener’s comprehension and memorization. This research is expected to contribute to the study of Arabic rhetoric (balagah) and broaden the understanding of expressive richness in the Arabic language.